X-Ray Crystallographic Studies of Nickel(II) Palladium(II) Complexes of o-Hydroxy Acetophenone Oxime - Mehta, B.H.; A. Swar, Yogesh (Asian Journal of Chemistry, 2010)
o-Hydroxyacetophenone oxime was synthesised by reacting o-hydroxyacetophenone with hydroxylamine hydrochloride. This oxime was used to synthesise nickel(II) and palladium(II) complexes having metal to ligand stoichiometry 1: 2. The ligand and metal- complexes were characterised by elemental analysis, molar-conductivity, electronic absorption and IR absorption spectra. The magnetic nature of the complexes was established using Gouy's balance method. The XRD data was used to index the compound for orthorhombic system with space group Pmmm or P222.